A novel phosphorylation-independent interaction between SMG6 and UPF1 is essential for human NMD. Issue 14 (22nd July 2014) - Nicholson, Pamela; Josi, Christoph; Kurosawa, Hitomi; Yamashita, Akio; Mühlemann, Oliver
Abstract: Eukaryotic mRNAs with premature translation-termination codons (PTCs) are recognized and eliminated by nonsense-mediated mRNA decay (NMD). NMD substrates can be degraded by different routes that all require phosphorylated UPF1 (P-UPF1) as a starting point. The endonuclease SMG6, which cleaves mRNA near the PTC, is one of the three known NMD factors thought to be recruited to nonsense mRNAs via an interaction with P-UPF1, leading to eventual mRNA degradation. By artificial tethering of SMG6 and mutants thereof to a reporter mRNA combined with knockdowns of various NMD factors, we demonstrate that besides its endonucleolytic activity, SMG6 also requires UPF1 and SMG1 to reduce reporter mRNA levels. Using in vivo and in vitro approaches, we further document that SMG6 and the unique stalk region of the UPF1 helicase domain, along with a contribution from the SQ domain, form a novel interaction and we also show that this region of the UPF1 helicase domain is critical for SMG6 function and NMD. Our results show that this interaction is required for NMD and for the capability of tethered SMG6 to degrade its bound RNA, suggesting that it contributes to the intricate regulation of UPF1 and SMG6 enzymatic activities.